2021
DOI: 10.1002/cpp.2641
|View full text |Cite
|
Sign up to set email alerts
|

Grief‐related beliefs in shidu parents with and without prolonged grief disorder: Psychometric properties of a Chinese version of the Typical Beliefs Questionnaire

Abstract: The Typical Beliefs Questionnaire (TBQ) assesses common grief-related cognitions, which demonstrated satisfactory psychometric properties in a treatment-seeking sample with prolonged grief disorder (PGD). Chinese shidu parents (bereaved parents over the age of 49 who have lost their only child) are at a high risk of PGD. The current study aimed to examine psychometric properties of the Chinese version of the TBQ (TBQ-C) in a community sample of shidu parents with and without PGD, to compare this to the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The flowchart of study inclusion and detailed characteristics of included studies are shown in Figure 1 and Table 1, respectively. Four studies assessed the presence of PGD by using the PG-13 based on the Prigerson et al ( 27) diagnostic criteria while two assessed the presence of PGD by using a self-developed scale based on the International Classification of Diseases 11th Revision (ICD-11) (15, 16,19,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The flowchart of study inclusion and detailed characteristics of included studies are shown in Figure 1 and Table 1, respectively. Four studies assessed the presence of PGD by using the PG-13 based on the Prigerson et al ( 27) diagnostic criteria while two assessed the presence of PGD by using a self-developed scale based on the International Classification of Diseases 11th Revision (ICD-11) (15, 16,19,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that about two‐thirds of the participants (Class 1 plus Class 2) have high endorsement probabilities for three counterfactual items, namely, the person did not have to die, should not have died like that, or should still be here. Such typical counterfactual thoughts were also highly endorsed by the treatment‐seeking sample with PGD in the United States (Skritskaya et al ., 2017), as well as Chinese bereaved parents who have lost their only child (Xu et al ., 2021). The results provide additional evidence to support that certain CFT are common and natural for bereaved people, regardless of the relationship to the deceased or the context or the time since loss.…”
Section: Discussionmentioning
confidence: 99%
“…Total scores of the TBQ were obtained by summing the 25 items. The Chinese version of the TBQ has been proven to have adequate psychometric properties in bereaved parents with and without PGD (Xu et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations